Maternal behaviours and considerations of breastfeeding practices in Malaysia during the Covid-19 pandemic - Ching, Xin Ni (2022)
Breast milk is an ideal food for infants to ensure their survival and immediate health. Since the COVID-19 outbreak in the late 2019, a few studies regarding the impacts of lockdown during the COVID-19 pandemic on breastfeeding have been reported. Various findings have been documented in different countries. However, none of this study has been done in Malaysia. Therefore, a cross-sectional study was performed in this study among Malaysian mothers with children aged less than two years old (n = 107) during COVID-19 pandemic. This was to explore the association of infant feeding practices and changes with the periods of delivery. Additionally, this study was aimed to investigate the association between changes in breastfeeding practices and three aspects which included maternal demographic characteristics, perceived effects of COVID-19 lockdown and perception towards possible reasons of changing breastfeeding practices. In this study, the actual breastfeeding practices for the first six months of babies had moderately changed (17.8%) from the mothers’ initial feeding intention before giving birth, in which the rate of exclusive breastfeeding was slightly decreased (4.6%) while the partial breastfeeding was moderately increased (12.1%) from the initial breastfeeding intention. The Fisher’s exact tests indicated a significant association between the feeding intention before delivery and periods of delivery (p = 0.002). Significant associations between changes of breastfeeding practices and four aspects such as maternal educational level (p = 0.007), total number of children (p = 0.026), perception of insufficient milk (p = 0.047) and embarrassment (p = 0.047). However, no association was found between any of the perceived effects of COVID-19 lockdown and changes of breastfeeding practices (p > 0.05). In conclusion, the breastfeeding-promoting interventions should be focused on the aspects that are significantly associated with the changes in breastfeeding practices as observed in this study.